Transtemporalidades na paisagem e cotidiano urbano: representações fotográficas de Uberlândia (1950-1960) - Viso, Guilherme Alves (2020)
The conception of modernity surges new discussions about iconographic discourse and visual culture as an important characteristic to the construction of a modern imagetic ideary of society. The emergence of photography modified the way we see the world: an almost realistic representation of reality, who commonly represents families, document histories and also a product of art. The photography can help us comprehend the city and the landscape that belongs to the urban and its memories. Transtemporal, allows that we can identify forms and functions which are volatiles during the historical process. Also allows that we understand the modern construction concepts, and we presents Uberlândia, a city located in the mesoregion of Triângulo Mineiro, who lives, idealizes and search for the modernity in a way of life quite conservative of an search for the walks for the west. Starting in the instrument of photography, we understand that the modernity and the changes in the quotidian occurs in a landscape in the 1950s and 1960s, a moment the world discusses a modernism crisis in the city. Besides that, we rescue these historical landscapes to comprehend the layers of the contemporary landscape.